Fried syndrome is a distinct X linked mental retardation syndrome mapping to Xp22. Issue 7 (July 1997) - Strain, L; Wright, A F; Bonthron, D T
Abstract : In 1972, Fried described a large Scottish family affected by X linked mental retardation (XLMR), hydrocephalus, and mild facial dysmorphism. The phenotype has considerable similarity to the MASA syndrome, which results from mutations of the L1CAM gene in Xq28, and this family has since been assumed to be an example of this condition. We have reinvestigated the family for linkage to X chromosome markers, and obtained additional clinical information on surviving affected subjects. The phenotype in these patients has evolved into a distinctive syndrome, with severe mental retardation (MR), spastic diplegia, ventricular dilatation, and calcification of the basal ganglia. Linkage to Xq28 markers has been excluded, suggesting that Fried syndrome is not allelic with MASA syndrome. Two point and multipoint linkage analysis indicates that the gene for this condition lies within the interval KAL-DXS989 in Xp22. We propose the designation Fried syndrome to emphasise the disorder's distinctive phenotype.